Determination of metal content in superoxide dismutase enzymes by capillary electrophoresis†. Issue 6 (12th February 2015) - Kazarjan, Jana; Vaher, Merike; Hunter, Thérèse; Kulp, Maria; Hunter, Gary James; Bonetta, Rosalin; Farrugia, Diane; Kaljurand, Mihkel
Abstract : Superoxide dismutases are antioxidant scavenger enzymes that contain a metal cofactor (copper, zinc, iron, and manganese) in their active site. Metal content measurement is one of the essential steps to characterize enzyme biological activity. We have developed a capillary electrophoretic protocol for the determination of the metal content in superoxide dismutase enzymes. The background electrolyte containing 10 mM pyridine‐2, 6‐dicarboxylic acid and 1 mM 1‐methyl‐3‐tetradecylimidazolium chloride at pH 3.8 was optimized for on‐column complexation of the above‐mentioned metals. The minimum detectable levels of metals ranged from 0.3 to 1.2 μg/mL. The reliability of the method was checked by parallel quantitative determination of the metal content in superoxide dismutase enzymes by graphite furnace or flame atomic absorption spectrophotometry methods.